Antimicrobial activity of seven metallic compounds against penicillinase producing and non-penicillinase producing strains of Neisseria gonorrhoeae. Issue 3 (June 1986) - Peeters, M; Vanden Berghe, D; Meheus, A
Abstract : The in vitro activity of seven metallic compounds was tested against penicillinase (beta lactamase) producing strains of Neisseria gonorrhoeae (PPNG) and non-PPNG strains. On a weight basis, the mercurials showed the greatest in vitro activity. Phenylmercuric borate, thiomersal, and mercuric chloride inhibited 90% of all strains at concentrations of 5 mg/l, 5 mg/l, and 20 mg/l respectively. Silver nitrate inhibited 90% of the strains at 80 mg/l and the MIC90 for mild silver protein was 200 mg/l. Copper and selenium salts had lower in vitro activities, inhibiting 90% of all the strains at 320 mg/l and 640 mg/l respectively. Silver nitrate and the six other compounds tested showed equal activities against PPNG and non-PPNG strains. This finding supports the recommendation for prophylaxis of gonococcal conjunctivitis of the newborn with 1% silver nitrate eye drops.